Osteonecrosis of the jaw in patients with multiple myeloma treated with zoledronic acid - (:unkn) unknown (SPRINGER JAPAN KK, 2009)
Intravenous bisphosphonates-the potent inhibitors of osteoclast-mediated bone resorption are among the most commonly prescribed drugs in the management of multiple myeloma (MM). Zoledronic acid (ZA) is a new generation potent intravenous bisphosphonate that has been approved for the treatment and prevention of bone lesions, and/or hypercalcemia associated with MM. Osteonecrosis of the jaw (ONJ) is an emerging serious side effect of the new generation bisphosphonates with a growing number of reports related to this pathological entity. ONJ usually appears following oral surgical and dental procedures but sometimes occur spontaneously. These cases are mostly seen and treated by dentists and oral surgeons. The aim of this study was to discuss the frequency, characteristics, risk factors, management and histopathological features of ZA induced ONJ based on the literature and illustrated with five own cases. Thirty-two patients with MM who received ZA for a median period of 26.5 +/- A 18.7 months (min: 5 months, max: 76 months) were evaluated. ONJ was detected in five patients and mean drug duration time was 34 months. The frequency was 15% and the patients were usually symptomatic. There was no significant difference in terms of the duration of ZA in patients with and without ONJ. Management of these established cases were performed with medical treatment, minor debridement, sequestrectomy, and combining bone resection with autologous platelet rich plasma. Our data indicate that ZA therapy has a major role in the development of ONJ a fact that should be considered by physicians treating MM patients.
Keywords: Multiple myeloma; Jaw osteonecrosis; Zoledronic acid; Bisphosphonates; Thalidomide; BISPHOSPHONATE-ASSOCIATED OSTEONECROSIS; CANCER-PATIENTS; RISK-FACTORS; INFECTED OSTEORADIONECROSIS; THERAPY; RECOGNITION; THALIDOMIDE; PREVENTION; MANAGEMENT; NECROSIS